南極昭和基地での宇宙線観測による宇宙天気研究 II - 宗像, 一起; 加藤, 千尋; 門倉, 昭; 片岡, 龍峰; P., Evenson; Kazuoki, Munakata; Chihiro, Kato; Akira, Kadokura; Ryuho, Kataoka; Paul, Evenson (2017)
第8回極域科学シンポジウム/個別セッション：[OS] 宙空圏 12月6日（水）統計数理研究所 3階セミナー室D304 The Eighth Symposium on Polar Science/Ordinary sessions: [OS] Space and upper-atmosphere sciences Wed. 6 Dec./3F Seminar room D304, Institute of Statistics and Mathematics conference object